Analisis Strategi Bisnis untuk Mencapai Keunggulan Kompetitif di UMKM Nukida Jati Bojonegoro - Ika Munawaroh; Elva Nuraina; Elly Astuti (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2021)
This study aims to identify business strategies implemented by MSMEs Nukida Jati to have a competitive advantage. The research method uses descriptive qualitative. Sources of data used are primary and secondary data sources. The technique of collecting data is the interview, observation, and documentation. Data analysis techniques used data reduction, presenting information data, and drawing conclusions. The calculation results of the IFE (internal factors) and EFE (external factors) matrices show that Nukida Jati MSMEs are in quadrant one. Combining these matrices in the SWOT analysis shows that the company's position allows it to maximize the opportunities and strengths. An alternative business strategy that can be applied to Nukida Jati MSMEs in this position is related diversification. This business strategy allows the company to produce various kinds of handicrafts with different specifications according to consumer demand with the same raw materials. Further product diversification can create wider market opportunities, especially if added with adequate digital marketing support